Antiviral Action of Synthetic Stigmasterol Derivatives on Herpes Simplex Virus Replication in Nervous Cells In Vitro - Petrera, Erina (2014)
Polyfunctionalized stigmasterol derivatives, (22S,23S)-22,23-dihydroxystigmast-4-en-3-one (compound 1) and (22S,23S)-3β-bromo-5α,22,23-trihydroxystigmastan-6-one (compound 2), inhibit herpes simplex virus type 1 (HSV-1) replication and spreading in human epithelial cells derived from ocular tissues. Both compounds reduce the incidence and severity of lesions in a murine model of herpetic stromal keratitis when administered in different treatment modalities. Since encephalitis caused by HSV-1 is another immunopathology of viral origin, we evaluate here the antiviral effect of both compounds on HSV-1 infected nervous cell lines as well as their anti-inflammatory action. We found that both stigmasterol derivatives presented low cytotoxicity in the three nervous cell lines assayed. Regarding the antiviral activity, in all cases both compounds prevented HSV-1 multiplication when added after infection, as well as virus propagation. Additionally, both compounds were able to hinder interleukin-6 and Interferon-gamma secretion induced by HSV-1 infection in Neuro-2a cells. We conclude that compounds 1 and 2 have exerted a dual antiviral and anti-inflammatory effect in HSV-1 infected nervous cell lines, which makes them interesting molecules to be further studied.